2019
DOI: 10.18805/ijar.b-1085
|View full text |Cite
|
Sign up to set email alerts
|

Effect of supplementing Moringa oleifera essential oils on milk quality and fatty acid profile in dairy sheep

Abstract: The effect of Moringa oleifera essential oils supplementation on milk quality and fatty acid profile was studied in Sicilo-sarde sheep. Twenty-four Sicilo-Sarde ewes were divided into three homogeneous groups (8 animals per group): the control (C), O-M1 and O-M2 groups. The control group (C) received a basal diet of oats hay with complementation to the reason of 500 g/ewe/day of concentrate feed. While, ewes of the experimental batches (O-M1 and O-M2) received further to the basal diet and concentrate, 0.3 ml … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…In contrast to the present results, Kalaitsidis et al (2021) recorded a significant improvement in milk yield and fat (6.39 vs. 5.95 %) with a mixture of oregano and thyme essential oils. The same tendency was observed with Moringa oleifera essential oil in ewe's milk and fat content (Selmi et al, 2020). In addition, Dorantes-Iturbide et al ( 2022) recorded higher milk production, protein, and lactose content in response to EO supply.…”
Section: Milk Production and Compositionsupporting
confidence: 60%
See 1 more Smart Citation
“…In contrast to the present results, Kalaitsidis et al (2021) recorded a significant improvement in milk yield and fat (6.39 vs. 5.95 %) with a mixture of oregano and thyme essential oils. The same tendency was observed with Moringa oleifera essential oil in ewe's milk and fat content (Selmi et al, 2020). In addition, Dorantes-Iturbide et al ( 2022) recorded higher milk production, protein, and lactose content in response to EO supply.…”
Section: Milk Production and Compositionsupporting
confidence: 60%
“…Also, and in concordance with the present results, Benchaar et al (2008) observed a similar impact of terpenes and EO on the milk and meat fatty acid profiles of dairy cows. However, Selmi et al (2020) recorded a significant effect of Moringa oleifera EO on the FA profile of Sicilo-Sarde ewe milk, whereas Yonjalli et al (2020) showed no change for palmitic acid with tannin extract given that the content of this FA in milk is related to its de novo synthesis, and the stearic acid in milk was significantly affected by tannin extract. Curiously, the supplementation by the same REO largely affected the lamb meat FA profile (Smeti et al, 2018), which could be due to the different used doses of the EO in both studies.…”
Section: Milk Fatty Acid Profilementioning
confidence: 89%
“…They showed that milk yield and composition were not significantly changed. Effects of M. oleifera essential oils (0.3 and 0.6 ml/day) supplementation on milk quality and fatty acid profile in dairy sheep were investigated by Selmi et al (2020) and revealed increased milk fat, unchanged protein, decease urea nitrogen, decreased saturated, and decreased unsaturated fatty acid profiles. Mendoza-Taco et al (2022) investigated the impacts of M. oleifera leaf extracts (20 ml) on the physicochemical characteristics of yogurt prepared from sheep milk.…”
Section: Milk Production and Compositionmentioning
confidence: 99%